Investigating Adaptive Reuse as an Integral Part of Public Art Activity Spaces - Sahharil, Muhammad Adlin; Mohamed, Wan Srihani Wan (MAJ - Malaysia Architectural Journal, 2022)
Repurposing old buildings and integrating it with the contemporary arts in heritage space seems like the current trend nowadays to get the community together towards a direction of art appreciation within the society. Bringing new to the old, adaptive reuse community art spaces are now abundant around the city, but they struggle to compete for attention in a place and some old buildings are abandoned, doomed for urban decay. Adaptive reuse can breathe new life to old buildings, providing a wide array of contemporary public arts which are crucial to today's cities. The study can venture into looking upon the preference of the society and artists in addresing the significance of adaptive reuse that can be considered as ‘art’ spaces and how it can engage the community through art activities. This research uses literature based methodology and case study site observations. The analysis is done to measure the impact of public arts on physical, social and economic aspects when engaging arts in adaptive reuse. Data collected will be analysed to validate relevant facts for adaptive reuse to integrate public arts that will benefit the usage by the local creatives and community. However, the limitations of this study is the constraints and volume of old buildings.